2014
DOI: 10.1016/j.jfda.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human cytokines by Cordyceps militaris

Abstract: Cordyceps (Cordyceps militaris) exhibits many biological activities including antioxidant, inhibition of inflammation, cancer prevention, hypoglycemic, and antiaging properties, etc. However, a majority of studies involving C. militaris have focused only on in vitro and animal models, and there is a lack of direct translation and application of study results to clinical practice (e.g., health benefits). In this study, we investigated the regulatory effects of C. militaris micron powder (3 doses) on the human i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…On the fifth day (second Sunday), unbiased food + 100 g baked bread were provided for lunch; and a blood sample was collected as above. The selection of blood collection time points was based on the assumption that the foods/functional foods have a relatively significant effect on the human body (including cytokines and metabolic enzymes) 2.5-3.5 h after eating [10][11][12][13]29].…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the fifth day (second Sunday), unbiased food + 100 g baked bread were provided for lunch; and a blood sample was collected as above. The selection of blood collection time points was based on the assumption that the foods/functional foods have a relatively significant effect on the human body (including cytokines and metabolic enzymes) 2.5-3.5 h after eating [10][11][12][13]29].…”
Section: Treatmentsmentioning
confidence: 99%
“…However, no animal can truly reflect the effects of foods on the human body. Through extensive research, we have established the cytokine network and central metabolic pathway (CMP) network to quantitatively evaluate the effects of foods on immunity and metabolism in the human body [8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a study of normal Korean cytokine levels, 110 subjects were studied [37], and in a study of normal American cytokine levels, 144 subjects were examined [38] to estimate the normal range of blood cytokine concentration. Serval studies have shown that no changes in blood cytokine levels have been observed following ingestion of multivitamin and mineral supplement [39], probiotic supplement [40], fish oil [41], and Cordyceps militaris [42], which are known to help improve immunity. This may be because the cytokine level increased during the test period and then returned to normal, or the number of subjects was small, indicating that the individual deviation range was not statistically significant.…”
Section: Effects Of Eap Against Colds and Flumentioning
confidence: 99%
“…In other research, another cerebroside isolated from C. militaris, cordycerebroside B, has exhibited marked inhibitory activity against protein tyrosine phosphatase 1B, indicating that C. militaris may possess hypoglycemic activity and be useful in type 2 diabetes (Sun et al, 2019). Moreover, six compounds isolated from C. militaris such as ergosterol, adenosine, cordycepin, ergosterol peroxide, tetracosanoic acid 2,3-dihydroxypropylester, and mannitol have shown strong procoagulant activity (Juanjuan et al, 2018), while a clinical study has revealed that oral administration of different dosages of C. militaris significantly decreased the activity of various cytokines, particularly inflammatory cytokines and chemokines, indicating that C. militaris can reduce excessive immune responses in diseases such as autoimmune disorders and cancers (Sun et al, 2014). Up until now, no reports have documented the effects of soya-cerebroside in RA.…”
Section: Introductionmentioning
confidence: 99%